HUBUNGAN KONSEP HEALTH BELIEF MODEL TERHADAP ASUPAN VITAMIN C DAN ZINK MAHASISWA FK UMSU SELAMA PANDEMI COVID-19 - CERI PERMATA AYUNI; AMALIA EKA DAMAYANTI (JURNAL ILMIAH MAKSITEK, 2022)
o break the chain of spread of covid-19, it is necessary to have prevention and control efforts related to the vulnerability and danger of covid-19 by increasing individual and community awareness and making changes to a healthier lifestyle. The concept of the Health Belief Model theory (HBM) is the first theory in the field of health related to health behavior. Health behavior, especially diet, is one thing that can be done as a preventive measure from covid-19 transmission by paying attention to nutritional intake. One of the nutrients that play a role in increasing immunity is vitamin C and zinc. This study aim To find out the relationship between the concept of the HBM and the intake of vitamin C and zinc by FK UMSU students during the covid-19 pandemic. This research method Analytical observation with cross sectional design. The data in this study were obtained from primary data using a HBM questionnaire and 24-hour food recall. Data analysis using Chi Square Fisher Exact test. The results showed that most of the respondents had a high perception of the severity of covid-19 disease (86.7%), benefits in increasing consumption of healthy foods (96.7%), support for healthy food consumption (93.3%). , and have confidence in implementing a healthy lifestyle (93.3%). Meanwhile, 53.3% of respondents have a low perception of susceptibility to covid-19 infection and 76.7% of respondents have a low perception of barriers to healthy behavior. Most of the respondents have the behavior of fulfilling adequate intake of vitamin C (60%) and zinc (60%). The results of the bivariate analysis between the HBM and the intake of vitamin C and zinc were p>0.05. The conclusion are There is no relationship between the concept of the HBM on the intake of vitamin C and zinc of FK UMSU students during the covid-19 pandemic.